1 + 2 1 + 3 1 + 4 1 + 5 … = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
@chakravarthy b , don't use all cap "RAMANUJAN SUM" as title or in text. All cap in text is equivalent to shouting in voice which is rude. Include everything in a formula "=?" in LaTex. Use three dots ... or \dots or \cdots not two dots for continue to infinity. It is a standard so need not explain. The multipication sighs × are unnecessary.
@Chew-Seong Cheong @Nnsv Abhiram
x + n + a = a x + ( n + a ) 2 + 2 a ( x + n ) + ( n + a ) 2 + ( x + n ) . .
Using this equation, the answer to the question , obtained by setting x = 2, n = 1, and a = 0.
to get info press here
Log in to reply
Yes, I was just deriving the equation for this simple case.
x + n + a = a x + ( n + a ) 2 + 2 a ( x + n ) + ( n + a ) 2 + ( x + n ) . .
Using this equation, the answer to the question , obtained by setting x = 2, n = 1, and a = 0.
to get info press here
Problem Loading...
Note Loading...
Set Loading...
Let f ( x ) = x + 1 , then
f ( x ) ⟹ f ( 2 ) = ( x + 1 ) 2 = x 2 + 2 x + 1 = 1 + x ( ( x + 1 ) + 1 ) = 1 + x f ( x + 1 ) = 1 + x 1 + ( x + 1 ) f ( x + 2 ) = 1 + x 1 + ( x + 1 ) 1 + ( x + 2 ) f ( x + 3 ) = 1 + x 1 + ( x + 1 ) 1 + ( x + 2 ) 1 + ( x + 3 ) 1 + ( x + 4 ) … = 1 + 2 1 + 3 1 + 4 1 + 5 1 + 6 … = 2 + 1 = 3